2002
DOI: 10.1080/07481180290087375
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Change in Mental Health Status During the First Two Years of Spousal Bereavement

Abstract: Patterns of change in mental health were identified for 118 recently widowed participants using the Integra Outpatient Tracking Assessment, Mental Health Index. Change was measured 4 times over the first 2 years of bereavement using a cohort sequential design. It was hypothesized that application of the psychotherapy phase model would have some use in understanding the various ways in which people grieve. The overall pattern of change in mental health was similar to that of the psychotherapy dosage and psychot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…The findings confirmed some of the hypotheses and partially confirmed others. The study was conducted in Israel, and the findings are congruent with results found in similar studies on the outcomes of widowhood, that were performed in other countries (Carnelley et al 1999;Diamond et al 1987;Morgan et al 1997;Nieboer et al 1998Nieboer et al -1999Ott and Lueger 2002;Pinquart 2002;Stewart et al 2001;Turvey et al 1999). This indicates the universality of the loss of a sense of meaning in life among the widowed.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The findings confirmed some of the hypotheses and partially confirmed others. The study was conducted in Israel, and the findings are congruent with results found in similar studies on the outcomes of widowhood, that were performed in other countries (Carnelley et al 1999;Diamond et al 1987;Morgan et al 1997;Nieboer et al 1998Nieboer et al -1999Ott and Lueger 2002;Pinquart 2002;Stewart et al 2001;Turvey et al 1999). This indicates the universality of the loss of a sense of meaning in life among the widowed.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to other psychological processes of change, a mourning process is needed for adjustment and change (Hegge and Fischer 2000;Lopata 1996;Ott and Lueger 2002;Rondo 1992Rondo -1993Sable 1991;Shuchter and Zisook 1993). Several studies on spousal loss in later life refer to the mourning process as one of growth rather than a return to former functioning (Fry 1998;Howie 1992Howie -1993van den Hoonaard 1997;Yalom and Liberman 1991).…”
Section: Late-life Widowhood and Meaning In Lifementioning
confidence: 95%
See 1 more Smart Citation
“…These findings are now treated as established scientific fact and have been widely cited in major professional journals, including American Psychologist (Bonanno, 2004), Journal of Personality and Social Psychology (Bonanno, Moskowitz, Papa, & Folkman, 2005;Bonanno, Wortman, et al, 2002), Psychiatric Annals (Reissman, Klomp, Kent, & Pfefferbaum, 2004), Journal of Clinical Psychiatry (Harkness, Shear, Frank, & Silberman, 2002), Suicide and Life-Threatening Behavior (Jordan & McMenamy, 2004), Applied and Preventative Psychology (Bonanno, Papa, & O'Neill, 2002), and Death Studies (Jordan & Neimeyer, 2003;Ott & Lueger, 2002;Sikkema, Hansen, Kochman, Tate, & Difranciesco, 2004;Wolf & Jordan, 2000). The findings were also reported in great detail in both the Handbook of Bereavement Research: Consequences, Coping, and Care (Stroebe, Hansson, Stroebe, & Schut, 2001) and the CFAH (2003) Report on Bereavement and Grief Research.…”
Section: Deterioration Effects In Grief Counselingmentioning
confidence: 99%
“…Many men would be distraught and become severely depressed if their wives would die suddenly, leaving them alone, and subsequently their health would suffer. [15][16][17] People also should prepare themselves for the eventual death of their spouses, close relatives and dear friends in order to prevent deterioration of their own health resulting from the death of dear persons. Men were anxious about their circumstances of daily life such as cooking, cleaning and washing.…”
Section: Questionnairementioning
confidence: 99%